1949
DOI: 10.1136/ard.8.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of So-called Palindromic Rheumatism with Gold Compounds

Abstract: A relatively rare form of arthritis was described by Hench andRosenberg in 1941 andin 1944. The syndrome is characterized by frequently recurring attacks of pain, swelling, redness, and disability involving usually one joint at a time, but sometimes multiple joints. The attacks last for short periods and then subside completely without leaving -joint residue. They considered it to be a " new disease ", an entity separate from rheumatoid arthritis and distinguishable clinically from other forms of recurring acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1950
1950
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…In one of the first reports in which gold was used in the treatment of PR, three patients with PR were evaluated 29 . A noticeable reduction in the frequency and severity of attacks happened in all of the patients in total doses of 375‐625 mg. Remission occurred in total doses of 575‐1175 mg. None of the patients developed radiographic changes or persistent arthritis during 6‐18‐month follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the first reports in which gold was used in the treatment of PR, three patients with PR were evaluated 29 . A noticeable reduction in the frequency and severity of attacks happened in all of the patients in total doses of 375‐625 mg. Remission occurred in total doses of 575‐1175 mg. None of the patients developed radiographic changes or persistent arthritis during 6‐18‐month follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…In a case series with three patients and in two case reports, no beneficial effect of colchicine in reducing attacks was reported. [29][30][31] Schwartzberg et al reported complete cessation of attacks in two and decreasing the duration and frequency of attacks in three of five patients with PR treated with colchicine (1-2 mg/d). 32 Diarrhoea was developed in two patients.…”
Section: Colchicinementioning
confidence: 99%
“…Tra l'altro, questo studio era stato disegnato fin dal 1937 (11), ma fu poi interrotto per lo scoppio della seconda guerra mondiale, anche se già nel 1945 lo scozzese Thomas N. Fraser (18) pubblicò i primi risultati parziali. L'indicazione fondamentale dei sali d'oro rimane l'AR, anche se risultati soddisfacenti sono stati poi ottenuti nell'artrite psoriasica (19), nei reumatismi cronici dell'infanzia (20) e nel reumatismo palindromico (21). Allontanandoci per un attimo dall'ordine cronologico, è opportuno accennare a questo punto all'auranofin, che è pur sempre un sale d'oro, ma che, a differenza dai sali d'oro tradizionali, è attivo per via orale.…”
Section: Rubricaunclassified